Globalização e integração territorial – o caso da região de Tefé no Amazonas - Kristian Oliveira Queiroz (Confins)
The article aimed to analyze the territorial integration in the region of Tefé, in Amazonas, through the performance of the globalization agents present in the city of Tefé and its region of influence. In particular, the performance of services and finances were studied, which fragilely integrate the region of Tefé into the contemporary geographical environment, leading to a relativized integration. The methodology of this study was based on a bibliographical research, interviews and fieldwork for the collection of primary and secondary data, as well as the use of institutional information. It was concluded that this relativized integration occurs due to the existence of a telecommunications network and services with limited infrastructures that damage the fluidity of relations and flows. Virtuous flows to regional development and flows that make a fragmentation of the territory were identified through the actions of globalization agents in this part of the Amazon region.